Constructing desirable professional identities: Linguistic analysis of student teachers’ reflection on project-based learning - Kosmanou, Elissavet; Vassilaki, Evgenia (Frontiers in Education, 2023)
Under the framework of linguistic discourse analysis, the study sets to explore the specific lexicogrammatical choices through which student teachers construct their role and the challenges they faced during their teaching in their written reflections. The study draws on forty (40) graduate student teachers’ reflective texts on project-based learning implementation during their practicum. By examining the grammatical means through which student teachers framed processes and participants and the semantic relations among them, the analysis foregrounds aspects of self-representation and the tensions faced in the construction of student teachers’ desired professional identities within their assessed reflective writing.